2013
DOI: 10.1155/2013/206367
|View full text |Cite
|
Sign up to set email alerts
|

The Haiti Breast Cancer Initiative: Initial Findings and Analysis of Barriers-to-Care Delaying Patient Presentation

Abstract: Background. In Haiti, breast cancer patients present at such advanced stages that even modern therapies offer modest survival benefit. Identifying the personal, sociocultural, and economic barriers-to-care delaying patient presentation is crucial to controlling disease. Methods. Patients presenting to the Hôpital Bon Sauveur in Cange were prospectively accrued. Delay was defined as 12 weeks or longer from initial sign/symptom discovery to presentation, as durations greater than this cutoff correlate with reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…In their multinational study, Jassem et al reported that the delay was shorter in women with an intermediate education level, in women who work, and in women who live in big towns or cities . Higher breast cancer mortality rates in low and medium‐income countries (LMICs) are thought to be due to diagnosis in advanced stages and barriers to accessing medical care . Advanced stage at presentation in LMICs and in certain racial, ethnic and low socioeconomic communities in developed world are mainly because of delay in presentation to physician from onset of symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…In their multinational study, Jassem et al reported that the delay was shorter in women with an intermediate education level, in women who work, and in women who live in big towns or cities . Higher breast cancer mortality rates in low and medium‐income countries (LMICs) are thought to be due to diagnosis in advanced stages and barriers to accessing medical care . Advanced stage at presentation in LMICs and in certain racial, ethnic and low socioeconomic communities in developed world are mainly because of delay in presentation to physician from onset of symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…This poor ratio of diagnosis to survival is often linked to difficulty in accessing care and poor availability of treatment options after diagnosis. [2][3][4][5] Screening and early diagnosis are limited and patients commonly present with advanced stage of disease limiting their outcomes despite treatment. Commonly cited or implied reasons for late diagnosis are often related in the literature to delay to care, both patient related delay, and provider (or system) delays.…”
mentioning
confidence: 99%
“…Previous studies suggested that longer time intervals between the onset of symptoms and the first health care visit were associated with older age, lower educational level and lower family income 11,12 , but few of such studies were performed in Brazil 13,14 , which limits the understanding of such factors regarding the breast cancer in our country.…”
Section: Introductionmentioning
confidence: 86%
“…The variable of interest was the self-referred time interval between the onset of the suggestive symptom of breast cancer and the date of the first medical visit. This variable was dichotomized -≤ 90 days and > 90 days -as this was the cut-off point used in other studies 11,16,17,18 . The presence of a palpable lump, skin and/or nipple retraction, hyperemia, bulging, abscess or pain in the breast, ulceration, nipple discharge, change in breast size, and the presence of axillary nodules were considered signs/ Cad.…”
Section: Methodsmentioning
confidence: 99%